The Contribution of HCN Channelopathies in Different Epileptic Syndromes, Mechanisms, Modulators, and Potential Treatment Targets: A Systematic Review - Kessi, Miriam; Peng, Jing; Duan, Haolin; He, Hailan; Chen, Baiyu; Xiong, Juan; Wang, Ying; Yang, Lifen; Wang, Guoli; Kiprotich, Karlmax; Bamgbade, Olumuyiwa A.; He, Fang; et al. (Frontiers in Molecular Neuroscience, 2022)
Background Hyperpolarization-activated cyclic nucleotide-gated (HCN) current reduces dendritic summation, suppresses dendritic calcium spikes, and enables inhibitory GABA-mediated postsynaptic potentials, thereby suppressing epilepsy. However, it is unclear whether increased HCN current can produce epilepsy. We hypothesized that gain-of-function (GOF) and loss-of-function (LOF) variants of HCN channel genes may cause epilepsy. Objectives This systematic review aims to summarize the role of HCN channelopathies in epilepsy, update genetic findings in patients, create genotype–phenotype correlations, and discuss animal models, GOF and LOF mechanisms, and potential treatment targets. Methods The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, for all years until August 2021. Results We identified pathogenic variants of HCN1 (n = 24), HCN2 (n = 8), HCN3 (n = 2), and HCN4 (n = 6) that were associated with epilepsy in 74 cases (43 HCN1, 20 HCN2, 2 HCN3, and 9 HCN4). Epilepsy was associated with GOF and LOF variants, and the mechanisms were indeterminate. Less than half of the cases became seizure-free and some developed drug-resistant epilepsy. Of the 74 cases, 12 (16.2%) died, comprising HCN1 (n = 4), HCN2 (n = 2), HCN3 (n = 2), and HCN4 (n = 4). Of the deceased cases, 10 (83%) had a sudden unexpected death in epilepsy (SUDEP) and 2 (16.7%) due to cardiopulmonary failure. SUDEP affected more adults (n = 10) than children (n = 2). HCN1 variants p.M234R, p.C329S, p.V414M, p.M153I, and p.M305L, as well as HCN2 variants p.S632W and delPPP (p.719–721), were associated with different phenotypes. HCN1 p.L157V and HCN4 p.R550C were associated with genetic generalized epilepsy. There are several HCN animal models, pharmacological targets, and modulators, but precise drugs have not been developed. Currently, there are no HCN channel openers. Conclusion We recommend clinicians to include HCN genes in epilepsy gene panels. Researchers should explore the possible underlying mechanisms for GOF and LOF variants by identifying the specific neuronal subtypes and neuroanatomical locations of each identified pathogenic variant. Researchers should identify specific HCN channel openers and blockers with high binding affinity. Such information will give clarity to the involvement of HCN channelopathies in epilepsy and provide the opportunity to develop targeted treatments.